A Review on Ethnomedicinal Claims of Solanum Trilobatum Linn. - Patel, Bansari S; Patel, Bhupesh; Kapdiya, Bhavana (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Plants play an important role in the health of millions of people’s life in many villages of India in their day-to-day life by its traditional usage. Solanum trilobatum Linn. from family Solanaceae is an important Indian medicinal plant. It is well known for its medicinal values in Siddha and Ayurvedic system of medicine. This plant is acknowledged in Ayurveda as ‘Agnidamini’, ‘Valli Kantakarika’, ‘Alarka’ & Thdhuvalai in siddha systems. Present review was carried out to collect all available information on ethnomedicinal claims & research updates pertaining of Solanum trilobatum Linn. from published literatures & books. Materials and Methods: Information regarding ethnomedicinal claim were reviewed by using the available books with special reference to medicinal plants compiled from books on ethnobotany and research articles available on internet till date. The obtained information was categorized as per vernacular names, locality, used parts, therapeutic claims, type and mode of administration along with ingredients and dosage forms of the preparations. Results: Solanum trilobatum Linn. has been widely used by Siddha traditional system & some folklore groups in cough, cold, asthma and many respiratory diseases. In addition, it is also reported for its anti-inflamatory, hepato-protective, anti-diabetic, anti-oxidant, analgesic, anti-microbial, immunomodulatory, anti tussive, mosquitocidal, anti-bacterial properties. This plant is used as traditional medicine for various disease condition. All parts of plants are used for internal administration. Conclusion: Scientific studies (pharmacological and clinical) on Solanum trilobatum Linn are needed to establish its multiple ethnomedicinal claims.